Nederlandsch muzikaal tijdschrift vol. 8, nos. 1-12 - Nieuwenhuijsen, W. J. F. (Utrecht Bosch, 1846)
Published in Utrecht for a decade, the Nederlandsch Muzikaal Tijdschrift was the direct predecessor of Caecilia (1844-1944), the longest running music journal in The Netherlands and one of Europe’s longest lived. Appearing somewhat irregularly, from one to three times each month, the Nederlandsch Muzikaal Tijdschrift was founded to “inform readers about important artistic events at home and abroad...to give impartial reviews of recent compositions...to promote the good, the truth and to be thorough.”The editorship of the journal changed several times in the course of its run: A. P. F. Seyff edited the journal from its inception to 1840; Dr. F. C. Kist to September 1844 when he left to found Caecilia; and, W. J. F. Nieuwenhuijsen (under the pseudonym Ernest van Wachten) until 1848. The Nederlandsch Muzikaal Tijdschrift is in large part devoted to Dutch musical life. The concert reviews offer a remarkable panorama of musical activities throughout most of the country, with emphasis on Amsterdam, Utrecht, The Hague and Rotterdam. The majority of the concerts are mixed: intermingling orchestral works, solo and ensemble instrumental works, and vocal music. Operatic performances in The Hague and Amsterdam are also reviewed. Of particular interest to the historian of music in The Netherlands is the vast number of performances of compositions by Dutch composers including Johannes Verhulst and J. B. van Bree. Among the news topics treated are the efforts of the Maatschappij tot Bevordering der Toonkunst [Society for the promotion of the art of music] to strengthen their membership and activities and to bring better musical education to a wider range of the population.
Bound in with 'Nederlandsch muzikaal tijdschrift vol. 6 nos. 1-15', 'Caecilia. Algemeen muzikaal tijdschrift van Nederland, vol. 1 nos. 1-9' & 'Nederlandsch muzikaal tijdschrift vol. 7, nos. 1-12'
Keywords: 19th Century (1801-1900); Music criticism; Periodical; Utrecht (Netherlands)